Quantum dynamical dissociation of quarkonia by wave function decoherence in quark-gluon plasma - Kajimoto, Shiori; Rothkopf, Alexander (Nuclear physics. A, Nuclear and hadronic physics, 2019)
In this study, we investigate the real-time evolution of quarkonium bound states in a quark-gluon plasma in an improved QCD based stochastic potential model. This model describes the quarkonium dynamics in terms of a Schrödinger equation with an in-medium potential and two noise terms encoding the residual interaction between the heavy quarks and the medium. The time evolution described by this equation is unitary, since the effective potential term is real-valued. At a glance this is at odds with lattice results, but we explain why it is actually not the case. We discuss the time evolution of the admixtures of bound states in a static medium and in a boost-invariantly expanding quark-gluon plasma. We draw two conclusions from our results: One is that the outcome of the stochastic potential model is qualitatively consistent with the experimental data in relativistic heavy-ion collisions. The other is that the noise plays an important role in order to describe quarkonium dynamics in medium, in particular it causes decoherence of the quarkonium wave function.